2008
DOI: 10.1038/nrg2224
|View full text |Cite
|
Sign up to set email alerts
|

Finding a match: how do homologous sequences get together for recombination?

Abstract: Decades of research into homologous recombination have unravelled many of the details concerning the transfer of information between two homologous sequences. By contrast, the processes by which the interacting molecules initially colocalize are largely unknown. How can two homologous needles find each other in the genomic haystack? Is homologous pairing the result of a damage-induced homology search, or is it an enduring and general feature of the genomic architecture that facilitates homologous recombination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
167
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(169 citation statements)
references
References 102 publications
0
167
1
1
Order By: Relevance
“…However, before recombination, there needs to be a search in which homologous genes can find each other. The slow process of random diffusion is incompatible with the rate of recombination, 1,2 suggesting that another mechanism is at play. What this might be is an important remaining question in molecular biology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, before recombination, there needs to be a search in which homologous genes can find each other. The slow process of random diffusion is incompatible with the rate of recombination, 1,2 suggesting that another mechanism is at play. What this might be is an important remaining question in molecular biology.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is evidence to suggest that before strand breakage occurs, identical intact double-stranded DNA segments may pair. 1,[9][10][11][12] It is also conceivable that homology recognition between intact DNA tracts may occur in other biological processes. One instance might be the silencing of multiple copies of the same gene.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in mice reported that a DSB-independent mechanism promotes homolog pairing during premeiotic S phase prior to DSB formation (Boateng et al 2013). The molecular mechanism of DSB-independent homolog recognition remains a mystery, although the aggregation of heterochromatin, noncoding RNA, the SPO11 protein, or sequence-specific DNA-binding proteins such as transcription factors are suggested to contribute to this process (Page and Hawley 2004;Barzel and Kupiec 2008;Dombecki et al 2011;Ding et al 2012;Boateng et al 2013).…”
mentioning
confidence: 99%
“…This finding might suggest that, upon DNA breakage, homology search between sister chromatids is faster than homologs in mitosis, likely because sisters are connected by cohesion. In fact, while compelling data indicate that meiosis specific proteinaceous structures, called the synaptonemal complex, connects the homologs facilitating DNA exchange, there are contradictory observations that homologs pair in mitotic cell cycle [9]. Bzymek et al also found that the levels of mitotic inter-homologue junctions are remarkably lower compared to those of meiotic junctions, although the rates of DSB formation were comparable in the two contexts.…”
mentioning
confidence: 94%